OPTICAL AND STRUCTURAL CHARACTERISTICS OF ZINC OXIDE THIN FILMS PREPARED BY SELF ASSEMBLED MONOLAYERS (SAMS) - Rifai, Abdulloh
Optical and structural characteristics of zinc oxide thin films deposited by self assembled monolayers (SAMs) have been studied. Zinc oxide thin films were prepared under different conditions on glass substrates which involved immersing time and annealing temperature. The microstructure and optical properties of ZnO was investigated by means of x-ray diffraction analysis, plan-view and crosssectional scanning electron microscope, and UV-visible spectrophotometer. The effect of changing immersing time from 10 hour to 20 hour has been thoroughly investigated. Optical transmittance decreased when the immersing time was longer because obtained thin films were thicker. Optical transmittance up to 89% in the visible range was obtained under optimal conditions. Based on the XRD data, thin films prepared by SAMs had the structure of polycrystalline which had three strongest peaks at (100), (002), and (101). It was found that the growth of thin films occurred based on mixed growth (Stranski –Krastanov). Higher fraction of densification occurred when thin films were annealed at higher temperature